Evidence chain of custody break and its effects in the Brazilian criminal proceeding - Menezes, Isabela Aparecida de (2018)
This article aims to address the evidence’s custody chain breaks and its effects in the Brazilian criminal proceedings. Every day the theme has become more important to the point of deserving a deeper examination of its meaning and relevance as a way of guaranteeing the reliability of the evidence produced in the criminal process, from its inception until the moment of its evaluation by the court, allowing the verification of its existential chronology. Moreover, the legal basis governing the institute at a national level should be explored in order to verify the consequences of its disregarding in the light of the constitutional principles. Finally, the article seeks to point out the consequences of the disregard or violation of the evidence’s custody chain, including the implications thereof, specially regarding the incidence of unlawfulness in the evidence’s source and its repercussion in the derived evidences.